Demographic Changes in the Cities of Lower Silesia in the Perspective of Sustainable Development - Rynio, Dorota; Zakrzewska-Półtorak, Alicja; Adamiczka, Hanna; Pluta, Agata (Zmiany demograficzne w miastach województwa dolnośląskiego w perspektywie zrównoważonego rozwoju, 2022)
The article discusses and evaluates, against the background of selected issues in the theory of urban demography concerning sustainable development, changes in the number of inhabitants in Lower Silesian cities, and to indicate possible development paths for individual categories of cities. All Lower Silesian cities are the subject of the study. The research covered the period 2000-2020. The cities are categorised into small, medium, and large, and their specific characteristics are primarily related to their location. The article uses a descriptive method, simple statistical methods, comparative analysis, and an expert method. The latter proposed the division of cities into categories in terms of demographic changes and sustainable development paths for individual city categories. The results show that Lower Silesian cities (as a group) are ageing, regardless of their size, yet a detailed case study indicated a relatively large group of cities (mainly small) with a growing population and growth potential.
Biblioteka Regionalisty = Regional Journal, 2022, Nr 22, s. 94-104
Keywords: city; population; sustainable development; age structure; miasto; liczba ludności; zrównoważony rozwój; struktura wiekowa